equações :
x=11
y=27
(x+y)^2-xy
Soluções para a tarefa
Respondido por
0
Olá!!!
Resolução!!!
x = 11, y = 27 , basta substituir na expressão.
= ( x + y )² - xy
= ( 11 + 27 )² - 11 • 27
= 38² - 297
= 1444 - 297
= 1147
R = 1147
Espero ter ajudado!!
Resolução!!!
x = 11, y = 27 , basta substituir na expressão.
= ( x + y )² - xy
= ( 11 + 27 )² - 11 • 27
= 38² - 297
= 1444 - 297
= 1147
R = 1147
Espero ter ajudado!!
Perguntas interessantes
Ed. Física,
11 meses atrás
Português,
11 meses atrás
Geografia,
11 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás